Unusual presentation of a life-threatening intraperitoneal haemorrhage after elective inguinal hernia repair. Issue 1 (3rd December 2018) - Chan, Kenrick Kai Chi; Khan, Shahab; Lewis, Christopher
Abstract : A 57-year-old man who was hypotensive at induction of anaesthesia was having intermittent episodes of hypotension after an uncomplicated and relatively bloodless open inguinal hernia repair of a large left-sided hernia . His hypotension was responsive to small fluid boluses. He did not show any tachycardia, had no abdominal pain, no signs of bruising or bleeding in his abdomen, flanks, or scrotum. Remained clinically well and alert throughout until being transferred to a tertiary centre. Eventually became haemodynamically unstable approximately 6 hours postoperatively. CT angiogram showed a large haemoperitoneum with active bleeding. Diagnostic laparoscopy revealed an actively bleeding inferior epigastric artery which was stopped. The patient received 2 units of red blood cells and made a full recovery.